2022
DOI: 10.1177/17411343221107569
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of substitution to generic drugs and physicians’ perceived exclusivity of substitution: A cross sectional survey among physicians

Abstract: The use of generic medicines facilitate access to treatment and reduce the overall health cost. Policies promoting generic substitution take into account many components such as quality and efficacy considering health stakeholders including physicians and pharmacists and identifying factors impacting generics prescription. The current study aimed to assess the association between the perception of physicians towards generics with their sex and age and their willingness to switch to generics after initial treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…12,13 Moreover, the odds of acceptance to switch to generic drugs after initial treatment were reported to be higher among older Lebanese physicians with more experience. 14 However, in a recent study targeting pharmacists, only 52% suggested substituting to generics and were not supportive of the current strategy adopted. 6 Nevertheless, a study conducted in 2018 reported that after 12 months of switching from a brand to a generic drug, the same health outcomes were observed in terms of outpatient visits, urgent care visits, hospitalisations and medication discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Moreover, the odds of acceptance to switch to generic drugs after initial treatment were reported to be higher among older Lebanese physicians with more experience. 14 However, in a recent study targeting pharmacists, only 52% suggested substituting to generics and were not supportive of the current strategy adopted. 6 Nevertheless, a study conducted in 2018 reported that after 12 months of switching from a brand to a generic drug, the same health outcomes were observed in terms of outpatient visits, urgent care visits, hospitalisations and medication discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…Health stakeholders tried to invest in preventing and controlling non-communicable diseases through several measures, such as smoking cessation campaigns, early detection, and lifestyle interventions [5]. To improve medication access and decrease health inequalities, governments encouraged generic drug prescription [6], substitution [7], and clarification of misconceptions to increase their acceptance and use [8]. This brief communication summarizes the challenges associated with non-communicable disease multimorbidity and suggests solutions to overcome these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…7 Older physicians and those with more years of practice had higher acceptance to substitute to generics after initial treatment with a brand drug. 8 The ministry of public health in Lebanon promoted the use of generic by implementing the unified medical prescription that allows pharmacists to substitute to generic drugs without referring to the doctors. 9 Nevertheless, the Coronavirus disease of 2019 (COVID- 19) pandemic has imposed several challenges leading to the shortage of medications due to the disruption of their supply chains.…”
Section: Introductionmentioning
confidence: 99%